KRITIK UNTUK BANK SYARIAH (ANTARA HARAPAN, KENYATAAN DAN PARADIGMA RAHMATAN LIL ALAMIN) (Fokus Ekonomi, 2008)
As a relatively young group of Banks  the earliest was established as late as  15 years ago), the establishment of Moslem Banks can be said to be exciting enough as they have been expected by the Moslem Society in Indonesia. Blessing Paradigm has been strived by Moslem banking by giving more additional services (value added), its meaning consequence of world and eternity. However, after 15 years emerge on the surface, performance of Moslem banking still far from expectation and paradigm of Blessing. There are four factors faced by Moslem Banks, firstly clients have accustomed to conventional bank, secondly Human Resources of Moslem Bank still low in understanding of Fiqih Muamalah, thirdly its product still a few, and fourthly Moslem Bank is impressed “exclusive” just for Moslem people. Solutions are socialization and education to society about Moslem Bank by increasing the quality of services, consumer satisfaction, justice orientation, and run the banking function as an intermediary. Key Words: Moslem Bank, Conventional Bank and Paradigm